417 Vibrational Spectroscopy: A Rapid Tool for Soft Tissue Sarcoma Assessment. (28th February 2022) - Noor Mohamed, M.S.; Almond, M.; Kendall, C.; Dudgeon, A.; Mansfield, J.; Stone, N.; Barr, H.
Abstract: Aim: Soft tissue sarcomas (STS) are a comparatively unusual cluster of tumours; they arise from mesenchymal tissues. Surgery remains the primary and the only potentially curative treatment for most STS subtypes. Existing intraoperative margin assessment techniques are inadequate and the current gold standard for resection margin assessment of STS is post-operative histopathology, but this takes weeks to finalize. Consequently, an augmented surgical technique established by real-time non-destructive recognition of clear margins is essential to diminish the risk of local relapse, decrease the resection area, and enhance the effectiveness of surgical resection of STS. Vibrational spectroscopy (VS) is a non-destructive evaluation of the atomic oscillation within a molecule. Every molecule has a unique set of vibrational modes called molecular fingerprint. We aim to use Raman spectroscopy to analyse biomolecular spectra of sarcoma and develop a potential tool for intra operative margin assessment Method: Human sarcoma was tissue obtained from the biobank at QEHB. The samples were identified as Lipoma and Liposarcoma. The samples underwent spectral measurement with the Raman microscope and the tissue samples were then sent for histopathological analysis. Results: The spectral evaluation clearly demonstrates the biomolecular difference between the two groups and has a potential to become an intraoperative tool. Conclusions: A positive resection margin is the ultimate prognosticator of local relapse. There is a need for a rapid and reliable tool that can offer surgeons with instant feedback during primary procedure.